Analysis of the policy of sending troublemaking children to military barracks by local governments (case study of the KDM policy in West Java) - Teuku Muhammad Arief; Margaretha Hanita (PINISI Discretion Review, 2026)
The policy of sending delinquent children to military barracks by the West Java local government aims to address the increasing juvenile delinquency by utilizing military discipline to build strong character and mental resilience. The initiative arose in response to growing concerns over youth involvement in violence, substance abuse, and negative social behaviors, which have raised alarm among parents and educators. This study explores the implementation of this policy using Narrative Policy Analysis (NPA), a method that examines the narratives surrounding the policy and its reception by different stakeholders, including the government, military, and the public. The research finds that while the policy is seen by supporters as an effective means of rehabilitation, offering structure, discipline, and emotional fortitude, critics argue that it violates child protection laws and may exacerbate the stigma and trauma for the children involved. Moreover, there are concerns about the potential for the policy to worsen the psychological well-being of these children by labeling them as “delinquents,” which could have long-term negative effects on their development. The study recommends a more holistic approach to juvenile rehabilitation that prioritizes human rights, psychological support, and family engagement. The implementation of such policies should consider not only the immediate behavioral outcomes but also the overall well-being and future prospects of the children involved, ensuring a balance between discipline and empathy.